THE EFFECTIVENESS OF DICTOGLOSS TO TEACH WRITING SKILL VIEWED FROM STUDENTS’ RISK-TAKING - Arif, Abdul (IKIP PGRI Pontianak, 2013)
This research is aimed at finding out whether : (1) dictogloss is more effective than dicto-comp to teach writing skill; (2) the students with high level of risk-taking have better writing skill than those with low level of risk-taking; and (3) there is an interaction between the teaching methods and students’ risk-taking in teaching writing skill. This research is an experimental study carried out at the English Education Department of STKIP-PGRI Pontianak in the Academic Year of 2012/2013. The results of the data analysis showed that (1) dictogloss is more effective than dicto-comp to teach writing skill; (2) the students with high level of risk-taking have better writing skill than those with low level of risk-taking; and (3) there is an interaction between teaching methods and students’ risk-taking to teach writing skill. Based on these findings, it can be concluded that dictogloss is an effective method to teach writing skill and the effectiveness of the method is influenced by the students’ level of risk-taking.Keywords: Dictogloss, Writing skill, Risk-taking